2007
DOI: 10.1097/ico.0b013e31802d82e8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Voriconazole as an Additive in Optisol GS

Abstract: Voriconazole seems to be safe as a fortifying agent for cornea storage medium. It significantly reduces the rate of positive fungal rim cultures and shows no signs of endothelial cytotoxicity as viewed by EM and by a bioassay of trypan blue and alizarin red.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 37 publications
0
41
2
1
Order By: Relevance
“…In addition, far fewer cases of fungal endophthalmitis have been reported in the literature after organ culture storage compared with after hypothermic storage. 6,7 Our results are in contradiction to a previous study by Ritterband and colleagues, 11 which found a significant reduction in the rate of positive fungal donor rim cultures with voriconazole-supplemented Optisol-GS compared with Optisol-GS alone (0 vs 7 of 533 positive rim cultures; P = .02). However, there were important differences in methods between the previous study and this study.…”
Section: Corneal Safety Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…In addition, far fewer cases of fungal endophthalmitis have been reported in the literature after organ culture storage compared with after hypothermic storage. 6,7 Our results are in contradiction to a previous study by Ritterband and colleagues, 11 which found a significant reduction in the rate of positive fungal donor rim cultures with voriconazole-supplemented Optisol-GS compared with Optisol-GS alone (0 vs 7 of 533 positive rim cultures; P = .02). However, there were important differences in methods between the previous study and this study.…”
Section: Corneal Safety Resultscontrasting
confidence: 85%
“…10 The organ culture medium commonly used in Europe contains the antifungal amphotericin B. 6 A previous US study 11 examined voriconazole as an additive to Optisol-GS and found that there was a significant reduction in the rate of positive fungal donor rim cultures with voriconazole-supplemented Optisol-GS compared with Optisol-GS alone. The aim of the present study was to assess the efficacy and safety of voriconazole and amphotericin B in reducing C albicans and C glabrata contamination of Optisol-GS under normal storage conditions.…”
mentioning
confidence: 97%
“…The antimicrobial agents tested in this study are active against all of these pathogens, and the concentrations used have been proven to be nontoxic for the corneal endothelium. 9,[16][17][18] Three different types of decay were identified: exponential-indicating a first-order chemical reaction, linearindicating a zero-order chemical reaction, and a 1-step decay. During the exponential decay (penicillin G and possibly amphotericin B, and streptomycin), indicating a first-order chemical reaction, a constant percentage of penicillin G is consumed per time unit.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ritterband et al 18 found a significant reduction in fungal contaminations in corneas stored in Optisol with voriconazole added. However, there were significant differences between both studies.…”
mentioning
confidence: 94%
See 1 more Smart Citation